2019
DOI: 10.1074/jbc.ra119.009510
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function relationships underlying the dual N-acetylmuramic and N-acetylglucosamine specificities of the bacterial peptidoglycan deacetylase PdaC

Abstract: Bacillus subtilis PdaC (BsPdaC) is a membrane-bound, multidomain peptidoglycan N-deacetylase acting on N-acetylmuramic acid (MurNAc) residues and conferring lysozyme resistance to modified cell wall peptidoglycans. BsPdaC contains a C-terminal family 4 carbohydrate esterase (CE4) catalytic domain, but unlike other MurNAc deacetylases, BsPdaC also has GlcNAc deacetylase activity on chitooligosaccharides (COSs), characteristic of chitin deacetylases. To uncover the molecular basis of this dual activity, here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…We have performed a more in depth in vitro and in silico analysis on AngCDA than previously reported for any other CDA. Concerning the pH and temperature optima, activity on chitin and chitosan polymers and activity on COS DP1-6, AngCDA is similar to already described CDAs 26,27,34,33 . We thus assume that our insight into this fungal CDA allows a deeper understanding of other CDAs of both bacterial and fungal origin.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…We have performed a more in depth in vitro and in silico analysis on AngCDA than previously reported for any other CDA. Concerning the pH and temperature optima, activity on chitin and chitosan polymers and activity on COS DP1-6, AngCDA is similar to already described CDAs 26,27,34,33 . We thus assume that our insight into this fungal CDA allows a deeper understanding of other CDAs of both bacterial and fungal origin.…”
Section: Discussionsupporting
confidence: 77%
“…So far, CDAs and other CE4 enzymes were mainly tested for their activity on different polymeric substrates like chitins, chitosans, acetyl xylans, peptidoglycans and their oligomeric counterparts. In recent years, for an increasing number of CE4 enzymes, the mode of action, referring to the different products that are generated over time, was investigated as well 2,4,25,26,27,28 . Computational methods, such as sequence and structure alignments as well as homology modelling and docking studies were used to complement these in vitro assays 2,27,28 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In B. subtilis, deacetylation of the N-acetylmuramic acid by the protein PdaC confers resistance against lysozyme attack (Fukushima et al, 2005;Kobayashi et al, 2012;Grifoll-Romero et al, 2019). Another protein, PdgA described in L. monocytogenes is responsible for a similar resistance mechanism inducing N-acetylation of the peptidoglycan; a study by Popowska et al (2009) showed that a L. monocytogenes strain lacking PdgA was more susceptible to lysozyme and mutanolysin.…”
Section: Mechanisms Of Amp Resistance In Gram-positive Bacilli Modifimentioning
confidence: 99%
“…While it is theoretically possible to produce all pentamers in this way using seven different CDAs, some will be difficult to produce and their yields can be expected to be low, and most of them will require chromatographic purification. Also, for two of these enzymes, PcCDA and BsPdaC [ 38 , 39 ], N -acetylating activity in the presence of excess amounts of acetate has not yet been shown experimentally, but is assumed hypothetically here. For many of the pentamers, different production routes can be designed but for clarity, only the most feasible one is indicated in the figure.…”
Section: Preparation Of Pacos Pentamers and Hexamersmentioning
confidence: 99%